Epistemic Humility in the Age of Assisted Dying - Riley, Sean (The Hastings Center report, 2025)
The current debate on medical assistance-in-dying (MAID) fails to acknowledge the limitations of empirical data and the influence that cognitive biases exert in interpreting evidence and formulating arguments. This paper examines the evidentiary foundations of the MAID debates by conducting a critical analysis of the methodological approaches to research on MAID. The paper advocates for epistemic humility in this debate, including the acknowledgment of the fallibility of MAID research, the incompleteness of understanding surrounding MAID, and the limited usefulness of empirical facts in determining ethical judgments. These factors cast doubts over the role data can play in shaping MAID discourse. Developing a well-balanced MAID policy necessitates an innovative research framework that not only prioritizes methodological rigor and data integrity but also integrates ethical deliberation with empirical research through a commitment to epistemic humility.